Preferensi Pasien Kanker Payudara Mengenai Komunikasi Interpersonal Dokter dalam Menyampaikan Berita Buruk - Anita Asmara; Ike Junita Triwardhani (WACANA: Jurnal Ilmiah Ilmu Komunikasi, 2023)
For a doctor delivering bad news to cancer patients is a challenging task. Because if communication in conveying bad news fails, it can lose the trust of patients and their families. The purpose of this study was to explore the preferences of breast cancer patients regarding physicians' interpersonal communication in conveying bad news. The research method was carried out using qualitative research with a case study approach. The informants for this study were three breast cancer patients who are members of the Bandung Cancer Fighting Family Community. In-depth interviews were conducted via zoom meeting. Semi-structured in-depth interviews were conducted to identify patient preferences through content analysis. The results of the study: The main categories that are patient preferences are the way doctors deliver bad news, medical information, doctor's interpersonal communication skills, the way doctors provide motivation, patient feelings, family support, patient acceptance of bad news in an Islamic perspective, patient expectations for empathetic communication doctor. Knowing the preferences of breast cancer patients when receiving bad news can help doctors deliver bad news with effective and empathetic interpersonal communication.